Unconventional Endovascular Treatment of Iatrogenic Ilio-Cava Fistula - Nogueira,Clara (2012)
Arteriovenous fistula (AVF) following lumbar discectomy is an uncommon, threatening complication. Endovascular treatment is increasing worldwide. A 58-years-old woman was admitted with iatrogenic ilio-cava AVF and right external iliac artery (EIA) occlusion. Several attempts, retrograde and antegrade, to cross EIA occlusion failed, with both guidewires progressing to vena cava. Goose neck snare was used to snare contralateral guidewire (on venous system) and it was exteriorized on femoral artery, followed by EIA angioplasty and endograft exclusion of the AVF. Tips and tricks, like the one described, are essential for any vascular surgeon.